Workshop Bagi Pelajar MAN 1 Pangkalpinang Untuk Menjadi Content Kreator - Ade Septryanti; Syafrul Irawadi; Hilyah Magdalena; Harrizki Arie Pradana; Yuri Prima Fittryani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Social media is currently very popular with the millennial generation, where the current millennial generation is required to have very high creativity and can produce content. A good content is produced because of the existence of personal branding and good public speaking from a creator. In the workshop students are given directions and techniques for how to build personal branding and public speaking in public, besides that students are taught how to make and produce a video to be recognized by many people. The community service activity was held at MAN 1 Pangkalpinang which was attended by 40 students. Students who were so excited when they received the material and were very active in asking questions.asked questions when the resource person gave the material.